Growth and metal-decorated catalytic applications of silicon nanowires: a review - Vishwakarma N.K.; Mahto S.K. (My University, 2025)
Metal or heterogeneous catalysis is one of the promising tools for chemical synthesis in synthetic laboratories and industries. However, heavy metals leaching into the environment produce a detrimental effect on human health and living organisms. Although, without a stabilizer, metal agglomeration is a major concern that limits its extreme utilization. Silicon nanowires (SiNWs), a 1D nanomaterial, is robust and reagents/solvent-proof material that provides enhanced dispersion area than other solid support and minimizes agglomeration of catalysts. In this review, we focus on a brief description of different growth techniques of SiNWs, thereof discuss the homogeneous decoration of several heavy metals over it for enhanced catalytic activity and minimal leaching. Further, we look at the recent achievements in the development of SiNWs in microfluidics systems, which deliver confined space and high surface-to-volume ratio attributed synergistic rate of reaction. © 2023, Indian Academy of Sciences.